Digital Literacy Inherency within Narratives Subject at SMP Kristen Palangka Raya - Novitasari, Silvi Indri; Natalia, Tessya Lonica; Pebrianto, Tori; Gresella, Yuni Esa (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Our intention of this research is to show the research subjects' narratives, namely teachers who teach at Palangka Raya Christian Junior High School, Central Kalimantan, when dealing with the governance and presence of digital literacy. Digital literacy has become a serious discourse in the form of important cabinet government programs (2019-2024). We used interview method as our qualitative research method by searching for data in the form of narratives to the research subjects. Narratives in audio form (smartphone recording) are then transcribed into verbatim transcripts and developed based on the reality of narratives in the field. Based on the narrative reality at field level, the author found that although digital literacy experiences obstacles in terms of facilities, there is hope that digital literacy will get room to move not only in schools, but also outside schools.